PENINGKATAN PRODUKSI BIOGAS KELOMPOK TERNAK DESA TIMUHUN KLUNGKUNG - Winaya, I N.S.; Hartati, R.S.; Ariastina, I. W.G.; Alit Swamardika, I B. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2017)
In an effort to meet the energy needs of society, especially in rural areas, the construction of a barn energy in every village is a must. The energy barns should be established by utilizing local energy potential of the source material, processed and utilized as the availability of energy, so as to create an energy independent village. One of the alternative energy has great potential to be developed in villages in Bali is the energy of biogas from manure. The village is selected as a place of devotion is the village of the District Timuhun Banjarangkan precisely at two farmer group that is group and Group Winangun Livestock Pigs Cattle Cempaka. The villages in Klungkung in general and in particular Timuhun village known as a very fertile agricultural area so that the availability of waste from agricultural waste and livestock waste is overwhelming. Expected to understanding blending technique substrate agricultural waste and animal dung as material biogas, biogas production in this area be increased and the number of farmers using biogas energy from agricultural waste and livestock waste be increased, so that it can be a reference for the development of biogas technology in Bali. Ultimately it will be seen synergy with biogas utilization in rural agribusiness activities can be noted that people in the groups are very enthusiastic to utilize organic wastes such as grass and plants mixed with livestock manure to produce biogas energy.